Assessment of the dental fear and anxiety in patients admitted to the Dental Clinic of Hue University of Medicine and Pharmacy Hospital - Nguyen, Thi Thuy Duong; Le, Thi Tai; Nguyen, Dinh Hoa (Tạp chí Y Dược Huế, 2024)
Background: Fear and anxiety in dentistry are among the factors that hinder access to dental care. This study aimed to assess the level of fear and anxiety regarding dental treatments and related factors. Materials and methods: This cross-sectional descriptive study included 300 patients aged ≥ 18 years who visited the Hue University of Medicine and Pharmacy Hospital for 5 months (12/2022 to 04/2023), The levels of dental fear and anxiety were assessed using DFS and MDAS. The relationship between dental fear and anxiety and the analyzed factors was examined using a multivariate logistic regression model. Results: Of the total sample, 52% had dentophobia, and 51.7% had dental anxiety. The incidence of dental fear and anxiety was higher in females compared to males, in individuals with a history of painful dental treatment than in comfortable ones, and individuals with irregular dental check-ups than in regular ones. Dental fear was also higher among single individuals. Conclusions: Fear and anxiety related to dental treatment were widespread among adult patients. Gender, marital status, treatment history, and frequency of dental visits were associated with dental fear and anxiety.